FT-IR, EDXRF analysis of the Mardin-Mazidag phosphate deposit of Turkey and relations between phosphate, uranium and fluorine - Çağlar, Hikmet; Çağlar, Nazan; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (ASIAN JOURNAL OF CHEMISTRY, 11/100 RAJENDRA NAGAR, SECTOR 3, SAHIBABAD 201 005, GHAZIABAD, INDIA, 2008)
EDXRF and FT-IR spectral analyses of the composite sample of Mardin-Mazidag phosphate deposit, in which the main phosphate mineral has been known to be collophane and dahllite, were reported. Uranium, phosphate and fluorine contents of the 25 individual phosphate samples were analyzed by EDXRF (U and P) and wet chemical methods (F). Quadratic regression model were applied on the U, P and F analyses results, in order to show the interrelation between phosphate, uranium and fluorine contents.
Keywords: collophane; dahllite; EDXRF; FTIR; phosphate minerals; quadratic regression analysis; fosfat mineralleri; kuadratik regresyon analizi